Tamoxifen Decreases Lithium-Induced Natriuresis in Rats With Nephrogenic Diabetes Insipidus - Tingskov, Stine Julie; Kwon, Tae-Hwan; Frøkiær, Jørgen; Nørregaard, Rikke (Frontiers in Physiology, 2018)
Lithium is widely used in the treatment of bipolar affective disorders, but often causes nephrogenic diabetes insipidus (NDI), a condition characterized by a severe urinary concentrating defect. Lithium-induced NDI is associated with dysregulation of the amiloride-sensitive epithelial sodium channel (ENaC), which is essential for renal sodium reabsorption. Sex hormones have been shown to affect the expression of aquaporin-2 (AQP2) and sodium transporters. Therefore, we evaluated whether tamoxifen (TAM), a selective estrogen receptor modulator, would affect lithium-induced dysregulation of ENaC subunits and natriuresis. Rats were fed with lithium-containing food for 2 weeks to induce NDI and natriuresis. TAM was administered daily via gastric gavage after 1 week of lithium administration. Lithium treatment alone resulted in increased urinary sodium excretion and significant reduction of βENaC and γENaC at both RNA and protein levels. In addition, the plasma sodium level reduced after lithium treatment. Administration of TAM prevented increased urinary sodium excretion as well as attenuated the downregulation of βENaC and γENaC. Consistent with these findings, immunohistochemistry showed stronger labeling of βENaC and γENaC subunits in the apical domain of the collecting duct cells in the cortical tissue of lithium-fed rats treated with TAM. Other major sodium transporters including NaPi-2, NKCC2, Na/K-ATPase, and NHE3, are believed not to have an effect on the increased urinary sodium excretion since their expression increased or was unchanged after treatment with lithium. In conclusion, the results demonstrated that TAM rescued the adverse effects of the lithium-induced increase in fractional excretion of sodium after the establishment of lithium-induced NDI.